ANALISIS PENERAPAN MANAJEMEN KAIZEN DI BIDANG INDUSTRI: STUDI KASUS PADA 3 PT DI INDONESIA - Yusuf Sugara; Adi Sopyan; Artia Tresnadi; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2021)
Kaizen technique is a lean production technique that applies the principle of perfection because it involves continuous improvement of work. In Indonesia, there are limited liability companies (PT) which have very rapid growth because kaizen culture. This shows that the kaizen culture affects the magnitude the magnitude of business competition. Therefore, kaizen which is one of the lean manufacturing techniques that envisions sustainable development. Based on the description above, research on the Analysis of Kaizen Management Applications in the Industrial Engineering Sector: Case Studies in PT Companies in Indonesia needs to be carried out with the aim of analyzing the effect of Kaizen implementation on the sustainability of companies. This research is a literature review study that contains data from several previous studies related to this topic. Based on the results of research conducted by several studies reviewed in this study, it can be concluded that PT. Hino Motors Manufacturing Indonesia is considered very good in implementing kaizen because kaizen culture will greatly affect the performance of employees and the effectiveness of the company. Kaizen culture has a significant influence on the performance of the employees of PT Surya Toto Indonesia. The kaizen system has a major influence on the performance of PT Bridgestone Tire in terms of Environment Safety